A Philosophy for Education : A Study in Aesthetic Rationality - Bolton, Neil (Educational Research E-Books Online, Collection 2024., 2025)
The book supports an argument for the crucial role of the aesthetic in a humanist education. It is structured around the philosophy of Giambattista Vico (1668-1744) who saw the poetic imagination as the first language through which humankind makes sense of its place within the world with myths and symbolic ritual. This is the search for the truth of identity and, ultimately, requires a self that examines its own experiences. That examination is the work of an aesthetic rationality that responds to life's contradictions through the use of metaphor: An historical perspective, ranging from the Renaissance, through the Romantic Movement, to Phenomenology, identifies the major characteristics of an aesthetic rationality, and concludes with recommendations for the school curriculum.